1998
DOI: 10.1175/1520-0485(1998)028<1410:ivodwf>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Interannual Variability of Deep-Water Formation in the Northwestern Mediterranean

Abstract: In the Gulf of Lions, observations of deep convection have been sporadically carried out over the past three decades, showing significant interannual variability of convection activity. As long time series of meteorological observations of the region are available from coastal stations, heat flux time series for the Gulf of Lions for the individual winters from 1969 to 1994 are derived by calibrating these observations against direct measurements obtained over the convection site. These heat fluxes are also co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
140
0
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(169 citation statements)
references
References 34 publications
(39 reference statements)
23
140
0
6
Order By: Relevance
“…In particular, the absolute magnitude of the marked interannual variations predicted by our model in both MLD and HF (Table 1) agree with those reconstructed by observations and numerical modelling by Mertens and Schott (1998) Gulf of Lions that roughly coincides with an area of well documented deep-water formation, often referred to as the MEDOC area (MEDOC, 1970). In this and other successive studies (Gascard, 1978;Marshall and Schott, 1999) the authors observed deep convection and a complete homogenization of the water column down to the bottom (>2000 m) over an area of 50-100 km in diameter.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…In particular, the absolute magnitude of the marked interannual variations predicted by our model in both MLD and HF (Table 1) agree with those reconstructed by observations and numerical modelling by Mertens and Schott (1998) Gulf of Lions that roughly coincides with an area of well documented deep-water formation, often referred to as the MEDOC area (MEDOC, 1970). In this and other successive studies (Gascard, 1978;Marshall and Schott, 1999) the authors observed deep convection and a complete homogenization of the water column down to the bottom (>2000 m) over an area of 50-100 km in diameter.…”
Section: Resultssupporting
confidence: 83%
“…The cyclonic circulation leads to an uplift of the isopycnals forming a dome centred on the south of the Gulf of Lions at 42 • N 5 • E. During winter the Mistral from the Rhone Valley and the Tramontana from the north side of the Pyrenees blow over the area. These winds are cold and dry and typically occur in strong bursts, lasting for a few days, that are able to erode the near-surface stratification and expose the weakly stratified waters underneath (Leaman and Schott, 1991;Mertens and Schott, 1998). Deep convection can then occur with a consequent nutrient enrichment of the upper layers that will fuel the next spring bloom.…”
Section: The Area Of the Bloommentioning
confidence: 99%
See 1 more Smart Citation
“…As far as the observed seasonal signal has its origin in the formation of deep water in the Gulf of Lions, a process with clear interannual variability [Mertens and Schott, 1998], this variability must be also important in the outflow through the Strait.…”
Section: Some Hints About Interannual Variabilitymentioning
confidence: 99%
“…Its peculiar latitudinal location, in a transitional area between tropical and mid-latitude variability and its complex geometry are important drivers for local phenomena characterizing its climate, such as lee cyclogenesis (Trigo et al, 2002), local winds of sustained speed such as Bora, Mistral, Etesian winds (Zecchetto and De Biasio, 2007), and deep-water formation (Mertens and Schott, 1998;MEDOC Group, 1970).…”
Section: Introductionmentioning
confidence: 99%